Pengadaan Mini Garden â€œMandaka Laksmiâ€ di RW 13 Nusukan, Banjarsari, Surakarta dalam Rangka Program Kampung Iklim (Proklim) - Zuhro, Nurul Shofiatin; Nita, Elen; Fimala, Aprilia; Anggreani, Cindy Nur; Putri, Azizah Amalia; Ayu Kusumaningrum, Dennisa; Fikriana, Nisa Inda; Puji Rahayu, Fakih; Alam, Ridwan Nur; Marshela, Sylvia Anggi; Larasati, Rima Fatima (Edumedia Solution, 2022)
The Climate Village Program (ProKlim) is a national scale program in order to encourage the community and all parties to take concrete actions to improve resistance to the negative impacts of climate change. In the village of Nusukan in particular RW 13 will be promoted by the Climate Village Program (ProKlim). To support the program, the procurement of a mini garden is carried out as an effort to move society and all parties in the face of climate change. The impact of this activity is to increase public knowledge and understanding of change climate and its impacts, as a real adaptation effort so that it can improve the degree of public health in the face of climate change, environment of RW 13 Nusukan, and can reduce GHG (Greenhouse Gas) emissions.